Uporaba metode sledenja delcev za modeliranje transporta in odmiranja bakterij Escherichia coli v morju - Lešek, Anja (Acta hydrotechnica, 2018)
We discuss modeling of the transport and decease of bacteria Escherichia coli in marine environments. We calculated the spatially variable decease coefficient of E. coli from the extrapolated measurement data on environmental parameters in accordance with Mancini's equation for bacteria stemming from the Rižana River and entering into the computational domain % the eastern part of the Koper Bay. Using pre-computed circulation data and the modified particle-tracking model Nafta3D we performed two-day simulations of an instantaneous and a continuous release from a single source. We analyzed locations of two particle types: free E. coli (ECF) and E. coli bound to suspended solids (ECA). We then analyzed the ECA and ECF activity decrease with a newly developed decease model, applying a first-order kinetics equation. In the given conditions a vast majority of ECA remained in the second basin of the Port of Koper and sank to the bottom layers. The decease time of 90% of the ECA (T90) was about 48 hours. The ECF remained closer to the surface; they moved more quickly and for the most part abandoned the second basin. The determined T90 was 6 and 10 hours in instantaneous and continuous release, respectively.
Keywords: activity; aktivnost; E. coli; environmental parameters; first order kinetics; Koper Bay; Koprski zaliv; Mancini equation; Mancinijeva enačba; model; okoljski dejavniki; razpadna enačba prvega reda; transport